The impacts of self-regulation and language learning anxiety on the English competence of university students in Aceh, Indonesia - Septhia Irnanda; Sabrina Sabrina; Cut Mulia Zuhra; Nora Fitria; Zaiyana Putri (Englisia: Journal of Language, Education, and Humanities, 2026)
Previous research has established that self-regulation plays a critical role in successful language acquisition. In parallel, language learning anxiety has been widely examined, though its influence is often understood through its negative relationship with self-regulatory abilities, suggesting that anxious learners struggle to deploy effective learning strategies. However, the direct and interactive effects of these two psychological constructs on English language achievement remain underexplored, particularly within Indonesian higher education contexts. To address this gap, the present study investigated the nature and extent to which language learning anxiety and self-regulation influence English language learning achievement among Indonesian EFL learners. Participants were 151 first-year university students from three faculties at Universitas Serambi Mekkah, Aceh, Indonesia, selected through cluster sampling. Data were collected using three instruments: (1) a validated self-regulation questionnaire, (2) a validated English language learning anxiety scale, and (3) a standardized test measuring general English competence. Regression analyses were employed to examine the predictive relationships among these variables. The findings showed that neither self-regulation nor language learning anxiety significantly predicted overall English competence. However, self-regulation showed a slightly greater contribution to English achievement than language learning anxiety, although neither effect was statistically significant. Notably, language learning anxiety significantly predicted self-regulation scores, indicating that anxious learners may struggle with self-regulatory capacity. Additionally, a weak positive correlation emerged between language learning anxiety and reading performance. These findings suggest that language learning anxiety does not directly determine competence success or failure; rather, it functions as a significant predictor of self-regulatory capacity and selectively influences specific language sub-skills such as reading comprehension.